Մահմուդ Ղազնավիին ուղղված երգիծանքի տեքստը մի ձեռագիր «Շահնամե»-ում (Մատենադարանի արաբատառ ֆոնդ, N535) - Կիրակոսյան, Հասմիկ («Նաիրի» հրատ.)
Начиная с XV века переписчики “Шахнаме” стали добавлять к поэме предисловия в прозе, включающие, как правило, данные о жизни Фирдоуси, события, отражающие отношения поэта с современниками, а также связанные с дворцовыми интригами, с историей создания «Шахнаме» и т. д. В этих предисловиях, помимо прочего, введен в оборот стихотворный текст сатирического послания Фирдоуси к Султану Махмуду Газневи, засведетельствованный еще с XII века и фигурировавший в ряде вариантов в разных рукописях. Предметом анализа данной статьи является одна из версий сатиры на Султана Махмуда (38 бейтов), приведенная в предисловии к рукописи “Шахнаме”, хранящейся за N 535 в арабо-персидском рукописном фонде Матенадарана и отличающейся содержанием и своеобразными разночтениями. Starting from the XV century, the “Shahnameh” scribes began adding prose prefaces to the poem, as a rule, describing details of the poet‟s life, persecutions of Firdausi by envious scribblers, court intrigues, as well as the story of the creation of the “Shahnameh” and subsequent events. These prefaces also introduced a short satirical poem on Sultan Mahmud of Ghazna, known from the XII century and attested in several versions in different manuscripts. The paper is devoted to the analysis of a unique version of the mentioned poetic piece (38 distichs) from the preface to one of the “Shahnameh” manuscripts of the Qajar period, kept in the Matenadaran (N. 535 Arabic Manuscripts Fund), and distinguished by its content, poetic devices and word usage.
Keywords: Բանասիրություն